2D and 3D radiographic outcome assessment of the effect of guided tissue regeneration using resorbable collagen membrane in the healing of through‐and‐through periapical lesions – a randomized controlled trial. (6th March 2019) - Parmar, P. D.; Dhamija, R.; Tewari, S.; Sangwan, P.; Gupta, A.; Duhan, J.; Mittal, S.
Abstract: Aim: To evaluate the effect of collagen membrane on the healing of through‐and‐through periapical lesions using 2‐dimensional (2D) and 3‐dimensional (3D) imaging techniques. Methodology: Thirty‐two patients with periapical radiolucencies measuring at least 10 mm and with confirmed loss of buccal and lingual cortical plates were randomly divided into GTR and control groups. Periapical surgery was performed in both groups, using a resorbable collagen membrane in the GTR group only. 2D healing was evaluated according to Molven's criteria, while 3D healing was assessed using modified PENN 3D criteria, RAC indices and the B index, 12 months after surgery. Data were analysed using Chi‐square, Mann–Whitney and Wilcoxon signed rank tests. Results: Thirty patients were analysed at the 12 months follow‐up. Both groups had a significant reduction in the size of lesions [92 ± 12% (control) and 86 ± 14% (GTR) in 2D and 85 ± 19% (Control) and 82 ± 13% (GTR) in 3D], with no significant difference between the groups ( P  > 0.05). A total of 29(14 control, 15 GTR) teeth and 26(13 control, 13 GTR) teeth were classified as success according to Molven's (2D) and modified PENN 3D criteria, respectively, with no significant difference in success between 2D and 3D assessments. RAC indices of 3D images revealed the greatest percentage of complete healing in R scores (55% for Control, 41% for GTR), whereas cortical plate had the lowest percentage of healing (30% for Control, 27% for GTR) ( P  > 0.05). Only 2 (13%) patients in each group had complete healing using the B index. Conclusion: Periapical surgery with or without GTR was a predictable and viable solution for through‐and‐through lesions. There was no benefit in using a collagen membrane with regard to the outcome of periapical surgery in through‐and‐through lesions. Both cone beam computed tomography (CBCT) and periapical radiographs (PA) allowed similar assessment of healing after periapical surgery.